Evaluation of partially dentate patients' knowledge about caries and periodontal disease - Ribeiro, Daniela Garcia; Jorge, Janaina Habib [UNESP]; Varjao, Fabiana Mansur; Pavarina, Ana Claudia [UNESP]; Nordi Sasso Garcia, Patricia Petromilli [UNESP] (Wiley-Blackwell, 2012)
Objective: This investigation evaluated the knowledge of dental caries and periodontal disease among removable partial denture (RPD) wearers.Method: A total of 127 partially dentate patients participated in this observational study. A structured questionnaire, which included eight questions referring to knowledge about aetiology and prevention of dental caries and periodontal disease, was developed in the local language (Portuguese) and used to collect the data of all the partial denture wearers. A descriptive analysis of data was performed by means of drafting tables.Results: The results demonstrated that 68.5% of patients interviewed had previously received information about oral health care. With regard to bacterial plaque, it was observed that only 34.6% reported having knowledge of this. Whereas, in relation to caries, 76.4% of the interviewees replied that they knew the meaning of this. Nevertheless, 28.3% referred to caries as a whole in the teeth, 16.5% as bad teeth and 9.4% bacteria/creatures on the teeth. Only 17.3% of the partially edentulous patients evaluated were shown to know what disease of the gingiva was.Conclusion: By means of the methodology applied, it could be concluded that the patients who wore RPDs presented deficient knowledge with regard to the prevention, aetiology and development of dental caries and periodontal disease.
Keywords: removable partial denture; oral hygiene; health education; dental caries periodontal diseases